Rethinking Uncaging: A New Antiaromatic Photocage Driven by a Gain of Resonance Energy. Issue 56 (2nd September 2021) - Hermanns, Volker; Scheurer, Maximilian; Kersten, Nils Frederik; Abdellaoui, Chahinez; Wachtveitl, Josef; Dreuw, Andreas; Heckel, Alexander
Abstract: Photoactivatable compounds for example photoswitches or photolabile protecting groups (PPGs, photocages) for spatiotemporal light control, play a crucial role in different areas of research. For each application, parameters such as the absorption spectrum, solubility in the respective media and/or photochemical quantum yields for several competing processes need to be optimized. The design of new photochemical tools therefore remains an important task. In this study, we exploited the concept of excited‐state‐aromaticity, first described by N. Colin Baird in 1971, to investigate a new class of photocages, based on cyclic, ground‐state‐antiaromatic systems. Several thio‐ and nitrogen‐functionalized compounds were synthesized, photochemically characterized and further optimized, supported by quantum chemical calculations. After choosing the optimal scaffold, which shows an excellent uncaging quantum yield of 28 %, we achieved a bathochromic shift of over 100 nm, resulting in a robust, well accessible, visible light absorbing, compact new photocage with a clean photoreaction and a high quantum product (ϵ⋅Φ) of 893 M −1  cm −1 at 405 nm. Abstract : The concept of excited state aromaticity was used to design a new class of photolabile protecting groups, based on cyclic, ground‐state‐antiaromatic systems. Supported by theoretical calculations, several thio‐ and nitrogen functionalized compounds were synthesized, characterized and further optimized, resulting in a well accessible, visible light absorbing, new photocage with a high uncaging cross section of 893 M −1  cm −1 at 405 nm.